NewsPaperBox - Online News Space: a visual model for representing the social space of a website - Selçuk Artut; Cem Öcalan (Journal of Systemics, Cybernetics and Informatics, 2010)

(untitled)
NewsPaperBox * propounds an alternative visual model utilizing the treemap algorithm to represent the collective use of a website that evolves in response to user interaction. While the technology currently exists to track various user behaviors such as number of clicks, duration of stay on a given web site, these statistics are not yet employed to influence the visual representation of that site's design in real time. In that sense, this project propounds an alternative modeling of a representational outlook of a website that is developed by collaborations and competitions of its global users. This paper proposes the experience of cyberspace as a generative process driven by its effective user participation.